Nurse Managers’ Utilization of Fayol’s Theory in Nursing - Joel Rey Ugsang Acob (State Islamic University of Sunan Ampel, 2018)
The main aim of this paper is to appreciate and evaluate human resource management practice of nurse managers utilizing Henri Fayol’s theory. The study being conducted to health facilities in Southern Leyte purposively employed sixteen respondents qualified based on the inclusion criteria such as having supervisory experience of atleast five years, either male or female and with permanent employment status. The study utilized descriptive-evaluative research design in order to collect information without manipulating or changing study subjects and its environment. Demogrpahic data were tabulated using simple percentage. Weighted mean was also used to establish different management practice delivered and implemented by nurse managers. Based from the findings, most of the nurse managers are female (87%), aging 40-47 years old, with an average gross individual monthly income of 17,000 to 25,000 thousand pesos. All of them did not have units of graduate degrees, however underwent trainings parallel to nursing practice. Education and supervisory-related trainings were acquired through shadowing and peer-coaching. Nurse Managers identified that the fast turnover of staff nurses is the leading factor affecting human resource management due to low salary rate of staff nurses. On the other hand, planning and controlling were the least among the five managerial roles delivered by nurse managers. The study recommends enhancement of these management components to effectively deliver care among clientele.